Laju dekomposisi bangkai mencit (Mus musculus) yang dikubur selama empat minggu pada media tanah humus, kapur, dan pasir pantai - Diarsa, Cakra; Junitha, I Ketut; Sundra, I Ketut (Jurnal Biologi Udayana, 2022)
Carcass will undergo decomposition as soon as organism dies, starting from tissue level up to molecular level of decomposition. Decomposition rate of buried carcasses is affected by three factors i.e., physical, chemical, and biological factors based on media used to bury carcass. Physical factors include structure, porosity, and humidity of media. Chemical factors include pH, sodium concentration, nutrients, and oxygen of media. Biological factors are number and composition of bacterial colonies, invertebrates, and flora that live on media. Purpose of this study is to investigate whether there are any differences in decomposition rates of mice carcasses based on different media for burying. This research was conducted using 36 mice carcasses which buried in plastic jars with 3 different media i.e., humus soil, beach sand, and limestone soil. Each of 12 plastic jars was filled with same media as replicates. Carcasses observed for 28 days, where every 7 days weight of mice carcasses weighed using digital scale and their physical condition were recorded and scored. Decomposition rate of mice carcasses will reflect through difference in average weight loss of mice (%) per week on each medium. The data analysis was done using the ANOVA test. Result shown that there was difference in average of weight loss and score of mice carcasses in each burying media. Conclusion of this research is the time and different media affected average weight loss and score of mice carcasses.